(untitled) (Global Journal of Management and Business Research, 2016)
The purpose of this research paper is to know the relationship between two ratios of the financial statements i.e. profitability and liquidity. The study is focused on the banking sector. The relation is measured by current ratio, quick ratio, and net-working capital. The bank under study is standard chartered bank Pakistan. From the findings of this study we came to conclusion that there is weak positive relation between liquidity and profitability. Quantitative research design is used as tool for the study. To find the relation and strength of the relation correlation and regression are used. So companies need to focus on liquidity management which has a positive relation with the company’s profitability.